Estilos de vida en los pacientes hipertensos adultos y adultos mayores que acuden al Subcentro de Salud de Rumishitana - Herrera Quezada, Johanna Lisbeth (2015)
This research was conducted in the neighborhood called ‘Rumishitana’, in ‘Malacatos’ parish during the period March - August 2014, in which several hypertensive adults and seniors participated as members of the rural Social Security. The study was justified because it has practical utility, convenient and generate benefits to society. The purpose was to determine the prevalence of hypertension and the lifestyles led by these patients, to determine that, the application of a survey with variables such as diet, nutritional status, physical activity, stress, and consumption of alcohol and cigarette, was necessary. Methodologically the is an observational-descriptive study where the universe is made up of 2192 people belonging to the Rural Security and the sample of 163 hypertensive affiliates. In the study, the prevalence was higher in female seniors. 70% of hypertensive overweight and obesity with blood pressure levels higher than normal weight. People prefer to consume simply carbohydrates in their 3 meals, and eat fruits and vegetables in small quantities. The 76% of respondents perform physical activity only, the 78% show stress, the 81% do not consume alcohol, and the 88% do not smoke. Therefore, it is important to educate people about healthy lifestyles to help control the disease and prevent early onset of complications. Keywords: Hypertension, lifestyles.